Elevated venous thromboembolism risk in preeclampsia: molecular mechanisms and clinical impact. (3rd August 2015) - Egan, Karl; Kevane, Barry; Áinle, Fionnuala Ní
Abstract : Venous thromboembolism (VTE) remains a leading cause of maternal death and morbidity in the developed world. Strategies for prevention of VTE in pregnancy have been the subject of recent guidelines and consensus statements. These guidelines recommend thrombosis prevention in women who have risk factors associated with an elevated VTE risk. Preeclampsia is characterized by maternal hypertension and proteinuria developing after 20 weeks gestation, complicating up to 7% of pregnancies and is associated with a massive annual morbidity and mortality burden. Women with preeclampsia have been shown to be at increased risk of VTE with studies to date suggesting that this risk may be up to 5-fold greater than the risk of pregnancy-associated VTE in the general population. Despite the fact that preeclampsia is so common and potentially devastating, our understanding of its pathogenesis and potential therapeutic strategies remain poor. In addition, the mechanisms underlying the prothrombotic phenotype in preeclampsia are also poorly characterized although a number of potential mechanisms have been postulated. Derangements of platelet and endothelial activation and impairment of endogenous anti-coagulant pathways have been reported and may contribute to the observed VTE risk. Recently, evidence for the role of neutrophil extracellular traps (NETs) and cell-free DNA in the pathogenesis of VTE has emerged and some evidence exists to suggest that this may be of relevance in preeclampsia. Future studies aimed at understanding the diagnostic and potential therapeutic relevance of this procoagulant state are likely to be of enormous clinical benefit for pregnant women affected with this potentially devastating condition.